3D full-field biomechanical testing of a glenoid before and after implant placement. (February 2020) - Zhou, Yuxiao; Gong, Chujie; Lewis, Gregory S.; Armstrong, April D.; Du, Jing
Abstract: Loosening of the glenoid component is the most common cause of failure of total shoulder arthroplasty. While the underlying mechanisms are not fully understood, mechanical factors are widely reported to play a key role in glenoid component loosening. In this study, mechanical testing coupled with micro X-ray computed tomography (micro-CT) is performed to apply various physiologically realistic loads on a native and implanted glenoid. Digital volume correlation of micro-CT images is used to compute the 3D full-field deformation and strain inside the glenoid. The measured strain distributions are in good agreement with the analytical solutions of beam bending models, especially for anteriorly and posteriorly eccentric loadings. The effective moduli of the overall native and implanted glenoid were similar. However, under the same eccentric loading conditions, implanted glenoid exhibited a wider range of strain, because the placement of glenoid component increases the bending moment inside the glenoid. This proof-of-concept study provides a feasible and powerful method for the study of 3D full-field biomechanics in native and implanted glenoids. Graphical abstract: Highlights: Mechanical testing coupled with micro X-ray computed tomography. 3D full-field deformation and strain inside native and implanted glenoid. Wider range of strain in the implanted glenoid than that in the native glenoid. Similar effective moduli for the native and the implanted glenoid. Increased bending moment inside implanted glenoid due to implant placement.